Reclaiming voices, rethinking change: a decolonial and knowledge-ecological analysis of SBCC nutrition interventions in Senegal - Faye, Sylvain L.; Sow, Georgette H. (Frontiers in Nutrition, 2025)
IntroductionSocial and Behavior Change Communication (SBCC) strategies have become central to nutrition interventions in Senegal, particularly to combat malnutrition and food insecurity among caregivers. However, improved nutritional knowledge has not consistently led to sustainable dietary practices. This study explores the limitations of conventional SBCC approaches through a decolonial and ecological lens of knowledge.MethodsThis qualitative study draws on ethnographic and participatory research conducted between 2020 and 2024 in Senegal. It focused on malnutrition, stunting, and food fortification initiatives—particularly those involving rice and broth cubes—to investigate the alignment between SBCC messaging and local food cultures.ResultsFindings reveal that prevailing SBCC models often rely on top-down, biomedical messaging shaped by Western nutrition science and state dietary norms. These interventions frequently overlook local food ecologies, sociocultural practices, and community knowledge, reinforcing technocratic and neoliberal framings while limiting community agency.DiscussionTo enhance relevance and sustainability, we advocate for a decolonial and knowledge-ecological approach to SBCC. This includes centering epistemic justice, fostering relational ethics, and co-creating interventions with communities. Integrating local perspectives and plural knowledges can better address the complex socio-ecological drivers of malnutrition.